Strategi Kyai dalam Membimbing Santri Menghadapi Media Digital Berbasis Hadits Akhlak - Fathur Rohman; Nasrulloh (Al-Kindi, 2026)
This research discusses the role and strategy of kyai in guiding students to face digital media challenges by using moral hadith as an ethical foundation. Pesantren are currently faced with changes in the behavior of students due to wide access to information, unlimited communication patterns, and the ease of obtaining content that is not in harmony with Islamic moral values. Through a qualitative approach based on content analysis, this study examines pesantren leadership literature, digital morals, and relevant hadiths. The results of the study show that kyai plays a central role as a spiritual guide, a supervisor of digital behavior, as well as an exemplary figure in responding to the flow of information. The coaching strategies found include supervision of the use of gadgets, habituation of manners through example, and the integration of hadiths such as "I am sent to perfect morals" and "Say good or be silent" in practical explanations of digital ethics. Kyai linked the prohibition of ghibah and slander with the phenomenon of hate speech and the spread of hoaxes, so that students understand the relevance of hadith to modern reality. This approach has proven to be effective in shaping the digital morals of students: they become more careful in commenting, more selective in choosing content, and realize that the use of digital media is part of their moral responsibility. This research emphasizes that the integration of hadith values, kyai examples, and spiritual guidance is an important foundation in building the character of students in the digital era.